Class II HLA-DC beta-chain DNA restriction fragments differentiate among HLA-DR2 individuals in insulin-dependent diabetes and multiple sclerosis. - Cohen, D (1984)
HLA-DR2 allele is negatively associated with insulin-dependent diabetes and positively associated with multiple sclerosis (MS). A 2.2-kilobase-pair EcoRI DNA restriction fragment detected with a beta-chain HLA-DC cDNA probe was found to be strongly correlated with HLA-DR2 in the normal population, but was absent in HLA-DR2 insulin-dependent diabetic patients. This fragment was found in HLA-DR2 multiple sclerosis patients with the same frequency as in controls. A beta-chain HLA-DC 12-kilobase-pair BamHI fragment might differentiate multiple sclerosis patients from healthy individuals.